Semiotics of the "third force" : MOST and the performative and visual dimension of political life in the post-electoral period in Croatia, 2015. - Falski, Maciej (Array, 2019)
The present paper analyzes the media representation of the idea of the "third force" in politics. The research focuses on how the notion is being staged and visualized in order to create the impression of a new and fresh agent in the race for power. The case of MOST, a political coalition which gained importance in the 2015 Croatian parliamentary election, seems particularly important and adequate for the purpose. I do not discuss programs, political aims or visions of the main political parties. Rather, I propose a semiotic analysis of public communication. Attention will be paid to performative aspects of television broadcasts, organization of the space where negotiations were held, visual relations between political actors. The broadcasts, and the broadly taken space of public contact, will be treated as a stage, and actions taking place on such a stage as a political drama, with a screenplay which may be, but is not necessarily, conscious and planned. When seen from this perspective, the focus of interest does not lie on the purposeful layout of seating in a meeting or a public communique, but on unconscious cultural patterns which have a great impact on our decisions, choices, and perceptions. Ultimately, the electoral success of MOST was related not only to its program, but also–or maybe mostly – to its performative policy and its consistent positioning as a new actor in the political field.